The effect of nitrogen on the growth of stock plant and subsequent rooting of cuttings of aquilaria microcarpa baill - Lim, Cherrie Han Rou (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Aquilaria sp. has high economic value but the shortage of seedling, poor seed germination and overexploitation has threatened the population. A study on the growth performance of A. fI1icrocatpa Baill. stock plants under different nitrogen (N) level (0 mg/L, 50 mg/L, 100 mg/L, ISO mg/L and 300 mglL) treatment and the subsequently rooting response of cuttings was conducted. Ammonium nitrate, NH4N03 was used as the N source. The treatment with 100 mglL of N showed the best result where the increment mean value of plant height, stem diameter and number of leaves was 20.64 em, 1.81 mm and 19 leaves, respectively. The poor increment was resulted in the control group (0 mg/L N), which was 0.94 cm, 0.65 mm and a decreased of I in the leaves number. 50 mglL N was also considered as a good treatment because the growth performance of stock plants were not significantly difference from those treated with higher N concentration. All the stock plants treated with N yielded sufficient healthy cuttings materials. Overall, the mortality rate of cuttings was high (32%) due to over misting. About 13% of the cuttings were rooted. Stock plant treated with 50 mg/L N proved to be good for the rooting of cuttings. No significant difference resulted in the rooting response of cuttings between hormone treatments. In terms of rooting performance, "Seradix I" gave the highest result in the number of visible roots and total root length compared with those without hormone or treated with "K-IBA".